FRI0462-HPR The effectiveness of physiotherapy exercises in subacromial impingement syndrome: A systematic review and meta-analysis. (23rd January 2014) - Hanratty, C.E.; McVeigh, J.G.; Kerr, D.P.; Basford, J.R.; Finch, M.B.; Pendleton, A.; Sim, J.
Abstract : Background: Exercise is a fundamental part of the management of subacromial impingement syndrome (SAIS), yet there has been relatively little examination of exercise interventions for this condition. Previous reviews in this area contain few randomized controlled trials (RCTs), have significant weaknesses, and none have conducted a rigorous meta-analysis of the data specifically related to exercise intervention. Questions remain regarding the overall effectiveness of exercise intervention in SAIS for example; which muscles should be targeted; and what is the optimal strengthening approach. The inconsistency of treatment and lack of guidelines may be reflected in the poor long-term outcome of conservative management of SAIS. 1, 2 Objectives: To evaluate the effectiveness of exercise in the treatment of people with SAIS. Methods: A systematic review and meta-analysis was conducted. Ten electronic databases were searched from the dates of their inception until August 2010. Included studies were RCTs investigating exercise in the management of SAIS. Outcomes were pain, strength, function, and quality of life. Data were summarised qualitatively using a best evidence synthesis. Treatment effect size and variance of individual studies were used to give an overall summary effect and data were converted to standardised mean difference with 95% confidence intervals (SMD (CI)). Results: Sixteen studies were included (total number of study participants=1162). There was strong evidence that exercise decreases pain and improves function at short term follow-up. There was also moderate evidence that exercise results in short term improvement in mental well-being and a long-term improvement in function, for those with SAIS. There was limited evidence that exercise reduced pain at long term follow-up. It was not possible to comment on the effect of exercise on long-term quality of life due to insufficient evidence. The most common risk of bias across the studies was inadequately concealed treatment allocation. Six studies in the review were suitable for meta-analysis. Exercise had a small positive effect on strength of the rotator cuff in the short term (SMD -0.46 (-0.76, 0.16); p=0.003), and a small positive effect on long-term function (SMD -0.31 (-0.57, 0.04); p=0.020). There was no statistically significant effect of exercise on short-term function. Conclusions: Physiotherapy exercises are effective in the management of SAIS. However, heterogeneity of the exercise interventions, coupled with poor reporting of exercise protocols, prevented conclusions being drawn about which specific components of the exercise protocols (i.e. type, intensity, frequency and duration) were associated with best outcomes. References: Desmeules F, Côté CH, Frémont P. Therapeutic exercise and orthopaedic manual therapy for impingement syndrome: a systematic review. Clin J Sports Med. 2003;13:176–182. Reilingh ML, Kuijpers T, Tanja-Hafterkamp AM, van der Windt DA. Course and prognosis of shoulder symptoms in general practice. Rheumatology. 2008;47:724–730. Disclosure of Interest: None Declared